Breeding programme and infrastructure: The case of Red Maasai sheep in Kenya - Zonabend König, Emelie (Swedish University of Agricultural Sciences, 2016)
The aim of this thesis was to study potential breeding strategies for indigenous livestock in Eastern and Southern Africa under low input production systems. The thesis covered a study of the status of supportive infrastructure for use of animal genetic resources. The case of Red Maasai sheep was studied as a model for design of strategies for improvement of an indigenous breed under threat. Studies [I-II] were performed through participatory approaches by use of structured interviews, while [III] comprised analyses of data collected at a research station, and [IV] was based on simulations. The infrastructure in the countries studied was weak and organizations needed more farmer involvement [I]. Countries with least university training in animal breeding also had least developed activities for animal genetic resources. A significant genotype by environment interaction was shown for Red Maasai and Dorper sheep in two different environments in Kenya [II]. Dorper was superior to Red Maasai for live weight in the less harsh environment, whereas breed differences were small in the harsh environment. Body size and milk production were highly ranked for both breeds. Red Maasai was appreciated for reproduction and adaptive traits and Dorper mainly for its larger body size. Dorper ram lambs were heavier live but did not have heavier carcasses than Red Maasai [III]. When basing their payment on assessed live weight, evaluators substantially undervalued Red Maasai lambs economically compared to Dorper. Opportunities for substantial genetic gain in live weight and carcass weight of Red Maasai sheep were shown in [IV]. When conditions are harsh, purebreeding of Red Maasai was superior to crossbreeding. The use of Dorper as a terminal sire breed to produce crossbred lambs for slaughter may be practised if environmental conditions are favourable and survival rates are high. It was shown that a nucleus breeding programme could sustainably improve the productivity of an indigenous breed, while contributing to biological diversity.